Learning Motivation of Undergraduate Nursing Students with Student Centered Learning (SCL) Learning Methods - Indriyani, Nur; Suparni, Suparni; Rejeki, Yunita Fitri; Erawan, Annisa Nur; Subekti, Trisno (Journal of English Language and Education, 2025)
Student-centered learning is student-centered learning. The application of student-centered learning in various universities has a diverse level of specialization in student-centered learning models and student motivation, so evaluating the application of learning models must be carried out in accordance with the needs of students and the applicable learning curriculum. Objective: This study aims to identify learning motivation in student-centered learning (SCL) of third-level nursing undergraduate students of STIKes Dharma Husada. Methods: This type of study uses an observational descriptive quantitative method with a sample of 82 respondents taken by purposive sampling technique. The instrument used was a learning motivation questionnaire in student-centered learning at STIKes Dharma Husada which referred to Cherniss and Goleman. Results: The results of the study seen from the frequency distribution showed that the motivation of level 3 nursing undergraduate students at STIKes Dharma Husada (67.1%) was in the medium category. In the aspect of motivation, 4 sub-variables, namely: Motivation to achieve something, Commitment, Initiative and Optimism are in the medium category. Student centered learning has 10 types of models. The first most popular student-centered learning model is the Role Play and Simulation model (41.5%) and the first least popular student centered-learning model is Small Group Discussion (34.1%). It is hoped that the study program nursing undergraduate can maintain the most in-demand model and evaluate and make the strategy of applying the student-centered learning model more attractive to the model that is not in demand.